Umieranie i śmierć : wielowymiarowość językowa - Wysoczański, Włodzimierz (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The author examines the problem of death and dying in the broadest possible linguistic multiplicity of dimensions and aspects. His analysis of the linguistic approach to dying, understood as a process, and the multi-faceted phenomenon of death inextricably linked to life covers human dying and death, dying and death in the non-human sphere as well as various references to these phenomena. In this sense the author’s exploration, ordering, recording and dissemination of the material selected from a huge corpus of various languages, reveals the linguistic testimony to death and dying from the past and its updating in the present. The analysed areas of dying and death as well as references to them are illustrated on the basis of examples derived from various languages and selected territorial varieties. The analysed material reflects a very broad variety of the language — territorial and communal, stylistic and chronological. The document base encompasses the literary variety of the language, territorial varieties, social varieties as well as stylistic varieties. The author explores general lexical items, substandard lexical items, specialist termin-ology, phraseology, paremiology, idioms, proper names, equivalents, synonyms, euphemisms, words derived from the same root, archaic expressions, obsolete expressions and neologisms.
Keywords: śmierć; tanatologia